2022
DOI: 10.1021/acs.jpcc.2c03984
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Phase Transition and Second-Harmonic Response Based on a Zero-Dimensional Organic–Inorganic Hybrid Compound

Abstract: The organic–inorganic hybrid materials (OIHMs) with stimuli-responsive features show the important scientific attraction in a multifunctional material application field, such as optoelectronic memory and sensors. Especially, designing a functional material with both dielectric switching and second-harmonic generation (SHG) remains attractive. Herein, we report a new OIHM [C7H15NCl] SbCl4 as a phase matching nonlinear optical material and dielectric switch functional materials. It undergoes a reversible phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…5c), and comparable to those of other materials such as [C 7 H 15 NCl]SbCl 4 (0.53× KDP). 60 The results confirmed that compound 1 can be used as a potential NLO material.…”
Section: Resultssupporting
confidence: 56%
“…5c), and comparable to those of other materials such as [C 7 H 15 NCl]SbCl 4 (0.53× KDP). 60 The results confirmed that compound 1 can be used as a potential NLO material.…”
Section: Resultssupporting
confidence: 56%
“…[31][32][33][34] Meanwhile, low-dimensional materials can provide a large degree of freedom for organic ammonium, thereby triggering the order-disorder phase transition. [35][36][37][38] As an example, Zou et al…”
Section: Introductionmentioning
confidence: 99%
“…40 In addition, our group synthesized the compound (CASD) 2 MnBr 4 (CASD = 8-chloro-5-azonia-spiro [4.5] decane), which exhibits a large SHG response. 33 Currently, most of the organic-inorganic phase transition perovskites reported are based on lead (Pb), [41][42][43] antimony (Sb), 37 bismuth (Bi), 44,45 cadmium (Cd), [46][47][48] and manganese (Mn). [49][50][51] In spite of this, there are still some problems associated with potential toxicity and environmental pollution, which limit the further applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations